Skin collagen peptides of Chinese giant salamander (Andrias davidianus) exert anti-inflammatory effects in LPS-induced RAW264.7 cells via the lincRNA-EPS/NF-κB pathway - Wencong Shang; Shuxian Su; Qinrong Li; Can Li (Food and Agricultural Immunology, 2024)
Food-derived collagen peptides have recently been reported to have immunomodulatory functions. The Chinese giant salamander (CGS) has both edible and medicinal values. In this study, we tried to verify the immunoregulatory function of CGS skin collagen peptides (CGSSCPs) on macrophages and elucidate its mechanism. CGSSCPs decreased the secretion of nitric oxide (NO) and downregulated the expression of interleukin-6 (IL-6), interleukin-1β (IL-1β), tumour necrosis factor-α (TNF-α), chemokine (C–C motif) ligand 5 (CCL5) and (C-X-C motif) ligand 10 (CXCL10) in Lipopolysaccharide (LPS)-induced RAW264.7 cells. Moreover, CGSSCPs promoted the expression of lincRNA-EPS, and inhibited the phosphorylation of nuclear factor kappa-B (NF-κB) in LPS-induced RAW264.7 cells. Silencing lincRNA-EPS up-regulated the phosphorylation level of NF-κB and the expression of inflammatory cytokines (IL-6, IL-1β, and TNF-α) and chemokines (CCL5 and CXCL10). These suggest that CGSSCPs may regulate RAW264.7 cells by the lincRNA-EPS/NF-κB pathway, which provides a theoretical basis for the development of new anti-inflammatory drugs.